1997
DOI: 10.1002/chem.19970030207
|View full text |Cite
|
Sign up to set email alerts
|

Hexabromotricyclobutabenzene and Hexabromohexaradialene: Their Nickel‐Mediated One‐Pot Syntheses and Crystal Structure

Abstract: The reaction of hexakis(dibromomethyl)benzene with [(Bu3 P)2 -Ni(COD)] (COD = 1,5-cyclooctadiene) in DMF at 65-70°C yielded a mixture of the title compounds. The mixture was separated by column chromatography to yield hexabromotricyclobutabenzene (3 a) and hexabromohexaradialene (4) in 24 and 16% yields, respectively. (1) H and (13) C NMR spectroscopy suggest that 3 is obtained as the syn-all-trans isomer 3 a, and the symmetric anti-all-trans isomer 3 b is not obtained at all. The X-ray structures of 3 a and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 31 publications
(3 reference statements)
0
17
0
Order By: Relevance
“…The structure of the new polymorph of the radialene 14 is, to the best of our knowledge, only the fifth of a simple radialene, the previously determined structures being the first polymorph of 14 [19] and the hexamethyl, [8] hexaethyl, [1b] and hexa-bromomethyl [22] derivatives. All these structures displayed crystallographic inversion symmetry and almost ideal chair conformations, with absolute ring torsion angles of ca.…”
Section: The Photochemical Isomerization Of Dodecamethyl[6]radialene mentioning
confidence: 96%
“…The structure of the new polymorph of the radialene 14 is, to the best of our knowledge, only the fifth of a simple radialene, the previously determined structures being the first polymorph of 14 [19] and the hexamethyl, [8] hexaethyl, [1b] and hexa-bromomethyl [22] derivatives. All these structures displayed crystallographic inversion symmetry and almost ideal chair conformations, with absolute ring torsion angles of ca.…”
Section: The Photochemical Isomerization Of Dodecamethyl[6]radialene mentioning
confidence: 96%
“…The MINDO/3-FORCES treatment of [6]-radialene showed that the chair form is more stable than the planar form. It is known that this method overestimates the H f values of cyclic planar unsaturated molecules by approximately 40% [16].…”
Section: Resultsmentioning
confidence: 99%
“…Since 1962 [1] these molecules attracted much attention because of their unique properties. Thus [6]-radialene may be considered as hexamethylene cyclohexane in which all ring carbons are sp 2 -hybridized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations